An Examination Of Settler Colonialism And Its Environmental Effects On The New Deal’s Public Artworks And Private Land Wall Paintings Throughout The Great Plains - Yanping, Wan; Muralitharan Doraisamy Pilla, Muralitharan Doraisamy Pilla (Journal of Neonatal Surgery, 2025)
This quantitative research looks at the Great Plains region of the researcher’s to see how private land murals and New Deal sculptures evolved and what effect they had. According to this study, New Deal artworks reflect and engage with issues of settler colonialism, environmental change, and cultural narratives. This study aims to shed light on the complex interplay between visual arts, settler narratives, and environmental changes in China during this formative era by employing a wide range of methodologies, including spatial analysis, statistical analysis of historical documents, and empirical analysis of art representations. The impact of the New Deal on population shifts and land use on the Great Plains and settler colonialism is the focus of this study. This research presents a methodical strategy for categorising and evaluating artworks produced by the WPA and the PWAP throughout the New Deal period. The researcher’s take a look at how they depict indigenous stories, farming techniques, and the connection between people and nature. Further, this study looks at how different forms of art have affected local communities, specifically how these forms of art have affected issues of identity, belonging, and the aftereffects of settler colonialism. By delving further into the themes of memory, exploitation, and preservation, the research reveals that these artistic depictions have ecological impacts. This study examines the connections between artwork placements and environmental data using GIS and statistical approaches. It demonstrates that art has real-world consequences on land and on communities. Results will encourage critical conversations on the complex processes of representation and reality in historical narratives of the geography of the United States, which will be useful for art history, environmental studies, and colonial studies.